EFFECTS OF LOW AND MEDIUM FREQUENCY CURRENTS IN THE TREATMENT OF URINARY INCONTINENCE: A RANDOMIZED CLINICAL TRIALRegistration: Not applicable. - Folegatti, Derfel Rodrigo Maciel Alba [UNESP]; Rita, Mell Moreira [UNESP]; Nagami, Danielle Hikaru [UNESP]; da Cruz, Douglas Cardoso [UNESP]; Gabini, Lívia Grous [UNESP]; Prudencio, Caroline Baldini [UNESP]; Barbosa, Angélica Mércia Pascon [UNESP]; Pedroni, Cristiane Rodrigues [UNESP] (Elsevier, 2025)
Background Urinary incontinence (UI) is defined as any involuntary loss of urine, classified as stress UI, urge UI (UUI) or mixed UI. UUI is caused by overactivity of the detrusor muscle and affects quality of life. Part of the first line of treatment for UUI is electrostimulation of the tibial nerve, but the literature is not clear on the effects of medium-frequency currents. One of the ways to measure some effectiveness is through the application of validated questionnaires, such as the Overactive Bladder Awareness Tool (OAB-V8), made up of 8 questions, which aims to assess the severity of overactive bladder symptoms and the discomfort caused by them. The scale ranges from 0 (no discomfort) to 5 (a lot of discomfort), with a maximum score of 40. A score of 8 or more suggests the presence of significant symptoms. Objectives To analyze and compare the Overactive Bladder Awareness Tool (OAB-V8) questionnaire score before and after treatment with low and medium frequency currents. Methods This is a randomized clinical trial, with women aged 18 years and over with complaints of UUI, randomly assigned to an intervention with low-frequency current (GTENS-LF) in a symmetrical biphasic pulsed form of 10 Hz and pulse width of 200 ms and another with medium-frequency current (GA-MF) with 4 kHz with bursts of 4 ms and modulation of 100 Hz in continuous mode. Both consisted of 20 sessions of bilateral electrostimulation of the tibial nerve, twice a week. The participants took an anamnesis and completed the Overactive Bladder Awareness Tool (OAB-V8) questionnaire. After 10 sessions the questionnaires were reapplied and at the end of the 20 sessions they were re-evaluated. Results A total of 50 participants were included and randomly assigned to two groups. At the evaluation, the participants obtained a score of 24.24 ± 8.72 in the GTENS-MF group and 28.52 ± 8.3 in the GA-MF group. At the 10th session, the results were 16.0 ± 64 and 19.6 ± 11.42, respectively. Finally, at the reassessment, GTENS-LF had scores of 13.72 ± 6.59 and GA-MF 19.06 ± 9.36. Conclusion In the context of this randomized clinical trial, it was observed that both low-frequency and medium-frequency currents were able to reduce the symptoms of overactive bladder and UTI when applied bilaterally to the tibial nerve, with no difference between the currents. Implications Based on the results of this study, the use of medium- and low-frequency currents becomes a viable alternative for the conservative treatment of patients with urge urinary incontinence.